A comprehensive inventory of the Gulf of Alaska sponge fauna with the description of two new species and geographic range extensions - Lehnert, Helmut; Stone, Robert P. (Zootaxa, 2016)
Two new species, Hamacantha (Vomerula) cassanoi n. sp. and Prosuberites salgadoi n. sp., are described from the eastern Gulf of Alaska in the North Pacific Ocean. These are the first records of the genera Hamacantha and Prosuberites from Alaska. We also report two geographic range extensions for the region. Geodia japonica Sollas, 1888 was previously known only from Japan and is now recorded from the Gulf of Alaska. We also document the first record of Rhizaxinella cervicornis Thiele, 1898 from the Gulf of Alaska. Our comprehensive inventory of the sponge fauna of the Gulf of Alaska confirms the presence of 52 taxa with an additional 38 taxa suspected of occurring in the region. This is a much lower number of species than that recorded from neighbouring regions like the Aleutian Islands and British Columbia.